Research methods, data collection, and data analysis in meetings, expositions, events, and conventions journals. Issue 5 (20th October 2021) - Draper, Jason; Liu, Yi; Young, Lisa
Abstract: There are many niche areas of research in hospitality and tourism, including meetings, expositions, events, and conventions (MEEC). Within such niche areas an assessment of the current status of the academic research is always helpful for current and future researchers. The purpose of this study is to assess the current status of research in MEEC journals and provide a roadmap for scholars as they aspire to publish in MEEC journals. This research conducts an analysis of 837 studies published in six MEEC-specific scholarly journals by analyzing event type, methods used, data collection techniques, and specific data analysis methods. Discussion includes guidance for submitting MEEC research, such as parameters on which journal might be the most appropriate target for a manuscript based on the research topic, data collection method, and data analysis approach. In summary, this article is a vital reference guide for academic scholars who want to advance their MEEC research in an effort to extend knowledge of our field.